2023
DOI: 10.1177/03946320231210736
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mitochondrial function in lymphocytes obtained from COVID-19 patients

Zhi He,
Jing-Jing Liu,
Shao-Lei Ma

Abstract: Objectives There is a significant decline in the lymphocyte subset counts in the peripheral blood of COVID-19 patients. However, the mitochondrial function of lymphocytes obtained from COVID-19 patients has rarely been studied. Methods A case-control study was conducted in 115 COVID-19 patients and 50 healthy controls from December 2022 to February 2023. The extent of lymphocytic mitochondrial damage in these patients using mitochondrial fluorescence staining and flow cytometry. Clinical symptoms were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that the CD3 + CD8 + SCMM may act as a diagnostic biomarker of COVID-19 progression. 19 According to our study, mitochondria may represent critical mediators and serve as strategic therapeutic targets in schizophrenia patients who were infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recent studies have shown that the CD3 + CD8 + SCMM may act as a diagnostic biomarker of COVID-19 progression. 19 According to our study, mitochondria may represent critical mediators and serve as strategic therapeutic targets in schizophrenia patients who were infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 82%
“… 34 Recent studies have demonstrated that mitochondrial function was severely impaired in lymphocytes of COVID-19 patients. 19 The higher SCMM in peripheral blood T lymphocytes reflects abnormal mitochondrial metabolism, which can result in decreased energy generation.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of infection, cells exhibit modifications in mitochondria characterized by thinner and elongated structures, suggesting morphological and dynamic fusion-fission related change [77]. The virus induces a rise in mitochondrial transmembrane potential resulting in elongated mitochondria and increased ATP synthesis, potentially contributing to viral replication and disease progression [78]. The virus therefore exacerbates the severity of disease by promoting the fusion and elongation of mitochondria, more effectively replicating within the host cells [76].…”
Section: Mitochondrial Fusion and Fissionmentioning
confidence: 99%